Craniofacial polyostotic fibrous dysplasia - Yadavalli Guruprasad; Chandan Prabhakar (Wolters Kluwer Medknow Publications, 2010)
An unusual case of fibrous dysplasia involving right craniofacial region in a female is reported. The clinical features, radiological findings, and treatment have been discussed.